2021
DOI: 10.1186/s13662-021-03341-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of taeniasis and cysticercosis transmission dynamics in humans, pigs and cattle

Abstract: Taeniasis and cysticercosis pose a significant challenge to food safety and public health. Cysticercosis reduces the market value for pigs and cattle by making pork and beef unsafe for consumption. In this paper, a mathematical model for the transmission dynamics of taeniasis and cysticercosis in humans, pigs and cattle is formulated and analyzed. The analysis shows that both the disease free equilibrium (DFE) and the endemic equilibrium (EE) exist. To study the dynamics of the diseases, we derived the basic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Our results indicate further that the treatment of infected humans is more effective when combined with adequate cooking of infected meat of cattle. Our previous study in Mwasunda et al (2021) on the transmission dynamics of taeniasis and cysticercosis in humans, pigs and cattle has shown that among other sensitive parameters, recruitment rate of humans, probability of humans to acquire taeniasis and the defecation rate by humans with taeniasis are the most sensitive parameters to diseases’ transmission whereas human natural mortality rate is the most negative sensitive parameter. These results agree with sensitivity indices of model parameters presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results indicate further that the treatment of infected humans is more effective when combined with adequate cooking of infected meat of cattle. Our previous study in Mwasunda et al (2021) on the transmission dynamics of taeniasis and cysticercosis in humans, pigs and cattle has shown that among other sensitive parameters, recruitment rate of humans, probability of humans to acquire taeniasis and the defecation rate by humans with taeniasis are the most sensitive parameters to diseases’ transmission whereas human natural mortality rate is the most negative sensitive parameter. These results agree with sensitivity indices of model parameters presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to control Taenia saginata bovine cysticercosis and human taeniasis, we suggest that more efforts should be directed to treat humans with taeniasis and improve meat cooking. The research work presented in this work differs from our previous study in Mwasunda et al (2021) in the sense that this study investigates the optimal controls for cysticercosis and taeniasis in cattle and humans only while the former study focused on analyzing the dynamics of taeniasis and cysticercosis in humans, pigs and cattle without any control measure. However, sensitivity analysis results in the two papers agree that humans recruitment and the defecation rate by humans with taeniasis are the most sensitive parameters in diseases’ transmission whereas human natural mortality rate is the most negative sensitive parameter.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
See 2 more Smart Citations
“…For the purpose of analysing the global stability of the DFE point, the controlled epidemic model is rewritten as [26,27]:…”
Section: Global Stability Of the Disease-free Equilibrium Pointmentioning
confidence: 99%